1991
DOI: 10.1016/0014-5793(91)80147-u
|View full text |Cite
|
Sign up to set email alerts
|

A heptapeptide repeat contributes to the unusual length of chloroplast ribosomal protein S18 Nucleotide sequence and map position of the rpl33‐rps18 gene cluster in maize

Abstract: The rpl33‐rps18 gene cluster of the maize chloroplast genome has been mapped and sequenced. The derived amino acid sequence of the S18 protein shows a 7‐fold repeat of a hydrophilic heptapeptide domain. S K Q P F R K, in the N‐terminal region. Such a sequence is absent in the E. coli S18 and in the chloroplast S18 of the lower plant liverwort. In tobacco and rice chloroplast S18 it is present 2 and 6 times, respectively. Thus a long N‐terminal repeat (resembling in composition the large C‐terminal heptapeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In both cases, L. perenne showed the shortest of all sequences. Sequence variation between monocots and dicots for rps18 has been described by Weglöhner et al, 33 based on the occurrence of different numbers of the heptapeptide repeat SKQPFRK near the N terminus of the protein. Our study revealed that length differences among Poaceae rps18 sequences are mainly based on the same heptapeptide repeat (S/F)K(Q/K)(P/T)F(R/L/H/S/N)(K/R) as described by Weglöhner et al 33 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, L. perenne showed the shortest of all sequences. Sequence variation between monocots and dicots for rps18 has been described by Weglöhner et al, 33 based on the occurrence of different numbers of the heptapeptide repeat SKQPFRK near the N terminus of the protein. Our study revealed that length differences among Poaceae rps18 sequences are mainly based on the same heptapeptide repeat (S/F)K(Q/K)(P/T)F(R/L/H/S/N)(K/R) as described by Weglöhner et al 33 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are three other proteins containing consecutive repeats of a heptapeptide or octapeptide whose structure and function may give some insight into variations in the CJD amyloid precursor structure. The maize ribosomal protein S18 has a 7-fold heptapeptide repeat at its N terminus that is thought to have some role in RNA binding (35). The DNA-dependent RNA polymerase II contains many repeats of a heptapeptide in its C-terminal domain, where a regular spacing of proline residues appears to be important in maintaining its unusual secondary structure.…”
Section: Resultsmentioning
confidence: 99%
“…5). The angiosperm S18 proteins have N-terminal extensions compared with E. coli, Marchantia polymorpha, and Cyanophora paradoxa, containing various numbers of repeats of a hydrophilic heptapeptide (686). A C-terminal extension found in the S18 proteins of rice and maize is missing from this protein in tobacco (561,686).…”
Section: Proteins Of the Small Subunitmentioning
confidence: 99%